Learning mimetic cuckoo call innovations from neighbors in a Chinese songbird - Changjian Fu; Xiaochun Wang; Fiona Backhouse; Zhongqiu Li (Scientific Reports, 2024)
Abstract Some oscine passerines incorporate heterospecific sounds into their repertoires, including vocalizations of other bird species, sounds of other fauna, and even anthropogenic sounds, through vocal mimicry. However, few studies have investigated whether mimics learn heterospecific sounds from model species or from conspecific tutors. Here, we investigate mimicry acquisition using innovation in Cuculidae calls imitated by the Chinese blackbird (Turdus mandarinus). If the mimicry innovation arises and spreads among several neighbors and is not produced by model species, the mimicry must be acquired partially from conspecifics. We found that: (1) Cuculidae calls imitated by blackbirds were reasonably accurate, but with some differences between mimetic and real calls in acoustic structures. (2) We identified four unique mimetic units (mimicry innovation or copy errors), and these units only occurred at certain sites and were shared by several neighbors. In aggregate, frequency parameters (the first principal component) of unique mimetic units were higher than usual mimetic units (p < 0.001). Our findings provide further evidence that mimetic units can be partially learnt from conspecifics based on four cases of unique mimetic units. Our study and approach provide a reference and theoretical basis for the future understanding of social learning and development of vocal mimicry.